A method for embedding FPC into wearable device mold
Patent Information
- Application Number
- CN202610228041.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-02-26
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2046-02-26
AI Technical Summary
[0005]针对现有技术的不足,本发明提供了一种FPC嵌入可穿戴设备模具的封胶方法,解决了FPC在低压注塑过程中因刚性不足导致的定位偏移问题,以及TPU封装层与FPC基材在湿热环境下界面结合力弱、易剥离的的问题
1.本发明通过在反应型触变界面锚定剂中引入疏水改性气相二氧化硅,并在FPC表面构建固态预凝胶层,利用气相二氧化硅形成的触变网络结构赋予预凝胶层较高的屈服应力。在模具装载及低压注塑充填阶段,该固态预凝胶层能够提供足够的静摩擦力,将柔性电路板稳定贴合于模具型腔内壁,有效抵抗热塑性聚氨酯熔体的流动剪切冲刷,防止柔性电路板在注塑过程中发生位移或卷曲,提高了封装尺寸精度和良品率。
Smart Images

Figure CN122100397B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of electronic packaging technology, specifically to a method for encapsulating FPC embedded in a mold for wearable devices. Background Technology
[0002] As wearable electronic devices evolve towards lighter weight and higher integration, low-pressure injection molding (LPI) is widely used in the encapsulation of flexible circuit boards due to its low injection pressure, fast curing speed, and excellent waterproof and sealing performance. This process typically uses thermoplastic polyurethane as the encapsulation material, placing the flexible circuit board and electronic components directly into a mold for injection molding to achieve structural protection and waterproof insulation.
[0003] However, flexible circuit boards are made of soft materials and lack rigidity, making it difficult to maintain a stable spatial position during mold closing and melt filling. Under the shearing action of the injection molten metal, flexible circuit boards are prone to displacement, curling, or deformation, leading to dimensional defects such as out-of-tolerance packages or even exposed copper. Existing auxiliary positioning methods, such as mold positioning pins, double-sided tape, or quick-drying adhesive dots, suffer from problems such as occupying wiring space, low efficiency of manual operation, or brittle adhesive layers that are prone to breakage, making it difficult to meet the yield requirements of automated production.
[0004] Furthermore, the interfacial bonding stability between the encapsulation material and the flexible circuit board substrate directly affects the product's weather resistance. Polyimide substrates have low surface energy and are chemically inert; the bonding between thermoplastic polyurethane and the substrate relies primarily on physical adsorption, resulting in limited bonding strength. In high-temperature and high-humidity environments, or under prolonged immersion in human sweat, water molecules can easily penetrate the interface and destroy the physical adsorption points, leading to delamination and subsequent circuit corrosion or short-circuit failures. While applying a primer can improve adhesion to some extent, conventional primers lack thixotropic setting capabilities and cannot simultaneously address positioning misalignment issues during injection molding. Summary of the Invention
[0005] To address the shortcomings of existing technologies, this invention provides a sealing method for embedding FPC into wearable device molds, which solves the problem of positioning misalignment caused by insufficient rigidity of FPC during low-pressure injection molding, as well as the problem of weak interfacial bonding and easy peeling between the TPU encapsulation layer and the FPC substrate in humid and hot environments.
[0006] To achieve the above objectives, the present invention provides the following technical solution: a sealing method for embedding FPC into a wearable device mold, comprising the following steps: S1, FPC pretreatment: Cleaning and activation treatment of the flexible circuit board surface; S2. Construction of thixotropic micropiles: A reactive thixotropic interface anchoring agent is coated at a preset position on a flexible circuit board. After drying to remove the solvent, a solid pregel layer with thixotropic properties is formed. S3. Mold loading: The flexible circuit board with the pregel layer is loaded into the injection mold cavity, and the friction between the pregel layer and the mold wall is used to suspend and fix the flexible circuit board. S4. Low-pressure injection molding encapsulation: Thermoplastic polyurethane melt is injected into the mold cavity. During the pressure holding stage, the heat of the melt is used to initiate a phase change, mutual solubility and cross-linking reaction in the pregel layer to complete the encapsulation. The reactive thixotropic interface anchoring agent is made from the following raw materials in parts by weight: 100 parts of polyester thermoplastic polyurethane, 400-420 parts of mixed solvent, 4-8 parts of hydrophobic modified fumed silica, 1.5-2.0 parts of silane coupling agent, and 10-18 parts of latent curing mixed micro powder. The latent curing mixed micro powder contains isophorone diisocyanate dimer resin and a temperature-sensitive catalyst. In step S4, the latent curing mixed micro powder undergoes a ring-opening reaction of the diurene ring under the activation of the injection molding melt temperature, forming a chemical bond with the thermoplastic polyurethane melt and the surface of the flexible circuit board.
[0007] By adopting the above technical solution, the present invention utilizes a reactive thixotropic interface anchoring agent to achieve a synergistic effect of physical confinement and chemical anchoring.
[0008] First, a thixotropic network is constructed in a polyurethane matrix using hydrophobically modified fumed silica, which, after drying, forms a solid pregel layer with yield stress. This pregel layer, acting as a physical positioning structure, uses static friction with the inner wall of the mold to fix the soft FPC at a specific position in the cavity, resisting the scouring force of the injection melt and ensuring the accuracy of the encapsulation position.
[0009] Secondly, a thermosensitive chemical crosslinking mechanism was constructed using latent curing mixed micropowders containing isophorone diisocyanate dimer resin and a thermosensitive catalyst. During the low-pressure injection molding holding stage in step S4, the heat from the injection melt is transferred to the interface, triggering an in-situ chemical reaction. Specifically, the high-temperature injection melt (200–210°C) contacts the pregel layer, causing the pregel layer to soften and interfacially dissolve with the melt, allowing the originally solid dispersed micropowder to enter a molten state. When the interface temperature reaches the range of 110–130°C, the activity of the thermosensitive catalyst in the micropowder is activated, causing the urea diketone four-membered ring in the isophorone diisocyanate dimer structure to break and open, releasing highly active isocyanate groups (-NCO). The generated isocyanate groups rapidly undergo addition reactions with urethane groups on the thermoplastic polyurethane molecular chain and active hydrogen on the FPC surface, generating thermally stable urethane bonds.
[0010] The reaction forms a semi-interpenetrating polymer network structure at the interface, transforming physical adsorption into chemical bonding. The dense cross-linked network effectively blocks the penetration of water molecules, improving the peel strength of the encapsulated product under humid and hot conditions of 85°C.
[0011] Preferably, the latent curing mixed micro powder is made from the following components in parts by weight: 100 parts of isophorone diisocyanate dimer resin; 34-37.5 parts of hydroxyl-terminated hyperbranched polyester; and 4-6 parts of DBU phenol salt thermosensitive catalyst.
[0012] By adopting the above technical solution, hydroxyl-terminated hyperbranched polyester is used as a co-curing agent. Its spherical structure and multiple terminal hydroxyl groups reduce the system viscosity and provide high-density reaction sites during micro-powder melting. DBU phenol salt is inert at room temperature, ensuring the storage stability of the micro-powder; at high temperatures (>110℃), it rapidly dissociates into the strong base DBU, reducing the activation energy of the urea diketone ring-opening reaction and ensuring a high conversion rate reaction is completed within the short holding pressure window (20–40 s) of low-pressure injection molding.
[0013] Preferably, the preparation method of the latent solidified mixed micro powder includes: premixing the isophorone diisocyanate dimer resin, hydroxyl-terminated hyperbranched polyester and temperature-sensitive catalyst at 20-25°C, then using cold compressed air at an inlet temperature of 5-10°C as the air source for airflow pulverization, controlling the outlet temperature to be below 35°C, and sieving to obtain micro powder with a particle size distribution D90 of 8.2-8.8 μm.
[0014] By adopting the above technical solution, a low-temperature cold air source is used for pulverization to prevent premature ring opening of the urea diketone ring or material agglomeration caused by mechanical friction heat generation. The particle size D90 is controlled within 8.2–8.8 μm to ensure uniform dispersion of the micro powder in the colloidal layer and to provide sufficient specific surface area for rapid response to thermal activation.
[0015] Preferably, in step S2, the preparation method of the reactive thixotropic interface anchoring agent is as follows: dissolve polyester thermoplastic polyurethane in a mixed solvent, add hydrophobically modified fumed silica and disperse it under high shear at a linear velocity of 18-20 m / s to construct a thixotropic base adhesive; then, under a temperature below 35°C, add a silane coupling agent and the latent curing mixed micro powder, disperse it uniformly at a low speed and degas it.
[0016] By adopting the above technical solution, a "stepwise dispersion" process is used: first, fumed silica is dispersed under high shear force to construct a thixotropic network, and then the micropowder is dispersed under low temperature and low shear conditions. This sequence prevents the failure of latent solidified micropowder caused by high shear heat generation, while ensuring the stability of the system's rheological properties.
[0017] Preferably, the mixed solvent is a mixture of butanone and ethyl acetate; and the silane coupling agent is γ-glycidyl etheroxypropyltrimethoxysilane.
[0018] By employing the above technical solution, butanone and ethyl acetate provide a balance between solubility and evaporation rate. γ-glycidyl etheroxypropyltrimethoxysilane acts as a bridging agent, coupling with hydroxyl groups on the surface of fumed silica to improve the compatibility and cohesive strength between the inorganic filler and the organic matrix.
[0019] Preferably, in step S1, the FPC pretreatment includes: baking and drying the FPC at 120°C, and then performing surface activation using an atmospheric pressure argon plasma cleaner with a processing power of 500W after cooling.
[0020] By adopting the above technical solutions, high-temperature baking removes moisture and prevents bubbles; argon plasma treatment breaks the surface molecular chains and introduces active functional groups, increasing micro-roughness and providing an interface basis for anchoring agent wetting and subsequent chemical reactions.
[0021] Preferably, in step S2, the drying process adopts one of the following methods: Method 1: drying at a constant temperature of 50-70℃ for 10-15 minutes; Method 2: first drying at 50-60℃ for 5-15 minutes, and then drying at 60-70℃ for 5-15 minutes.
[0022] By adopting the above technical solution, an adaptive drying strategy is used for coatings of different thicknesses, and the maximum temperature is controlled to not exceed 70°C. This removes the solvent while preventing the micropowder from melting, ensuring that the pregel layer maintains solid hardness before being placed into the mold to meet positioning requirements.
[0023] Preferably, in step S4, the low-pressure injection molding encapsulation adopts a two-stage process: the first stage: filling 90% of the cavity volume at an injection speed of 6-10 mm / s; the second stage: maintaining a holding pressure of 2.0-3.0 MPa for 20-40 seconds; wherein, the barrel temperature of the thermoplastic polyurethane melt is 200-210°C, and the mold temperature is 25-45°C.
[0024] By adopting the above technical solution, the first stage of low-speed injection prevents melt turbulence from damaging the pregel layer; the second stage of high-pressure holding promotes melt penetration and provides the free volume required for molecular chain movement, which, together with the enthalpy provided by the barrel temperature, drives the chemical reaction.
[0025] This invention provides specific configurations of the anchoring agent for different application scenarios: For small FPCs or visual alignment requirements, reduce the amount of hydrophobic modified fumed silica to 4 parts to form a semi-transparent pregel layer; For large-size or easily warped FPCs, the amount of hydrophobic modified fumed silica is increased to 8 parts, and high cross-linking density micro powder is added to improve the modulus of the pregel layer and enhance its erosion resistance. For low-temperature molds or short molding cycle processes, the content of temperature-sensitive catalyst in the micro powder is increased to reduce the reaction activation energy and ensure that cross-linking is completed at a lower interface temperature.
[0026] This invention provides a sealing method for embedding FPC into a wearable device mold. It has the following beneficial effects: 1. This invention introduces hydrophobically modified fumed silica into a reactive thixotropic interface anchoring agent and constructs a solid pregel layer on the FPC surface. The thixotropic network structure formed by the fumed silica imparts a high yield stress to the pregel layer. During mold loading and low-pressure injection filling, this solid pregel layer provides sufficient static friction to stably adhere the flexible circuit board to the inner wall of the mold cavity, effectively resisting the flow shearing and scouring of the thermoplastic polyurethane melt, preventing displacement or curling of the flexible circuit board during injection molding, and improving packaging dimensional accuracy and yield.
[0027] 2. This invention utilizes the heat generated by the melt during low-pressure injection molding to initiate a chemical reaction in situ by adding a latently curable mixed micropowder containing isophorone diisocyanate dimer resin and a temperature-sensitive catalyst to the anchoring agent. During the holding pressure stage, the high-temperature melt causes the micropowder to melt and activate the catalyst, inducing the ring-opening of the urea diketone ring to generate highly active isocyanate groups, which then crosslink with the active hydrogen on the surface of thermoplastic polyurethane and FPC to form urea-formate bonds. This chemical bonding replaces traditional physical adsorption, significantly enhancing the interfacial bonding strength and solving the problem of interfacial delamination of the encapsulation layer under high temperature and high humidity environments.
[0028] 3. This invention introduces hydroxyl-terminated hyperbranched polyester as a co-curing agent, utilizing its low melt viscosity and high functionality to improve the diffusion and wetting properties of micropowders in the molten state, and constructs a dense semi-interpenetrating polymer network structure at the interface. This structure not only enhances the cohesive strength of the encapsulation material but also effectively blocks the penetration path of water molecules to the interface, thereby improving the long-term protective reliability of wearable devices under conditions of human sweat corrosion or harsh damp heat testing. Attached Figure Description
[0029] Figure 1 The following are comparison diagrams of the rheological properties and thixotropic behavior of the present invention. In the figure, (a) is a comparison diagram of the static yield stress values of each sample, (b) is a comparison diagram of the apparent viscosity of each sample at low shear rate and high shear rate, and (c) is a comparison diagram of the calculated thixotropic index of each sample. Figure 2The following are comparative differential scanning calorimetry curves of the curing process of the reactive thixotropic interface anchoring agent of the present invention. In Figure (a), the heat flow curve of Example 1 shows both physical melting and chemical curing characteristics. Figure (b) is the heat flow curve of Example 4 after increasing the amount of catalyst. Figure (c) is the heat flow curve of Comparative Example 5 showing only physical melting characteristics. Figure 3 Figure (a) shows the statistical chart of the FPC position offset and anti-impact adhesive capability after encapsulation in the embodiment of the present invention, and Figure (b) shows the statistical chart of the position offset of the failure group of the comparative sample and the statistical chart of the position offset of the qualified group of the sample in the embodiment. Figure 4 The following is a statistical chart for evaluating the macroscopic defects and bubble rate of the interface in this invention. In the chart, (a) is a statistical chart of the interface bubble density at each observation point, (b) is a statistical chart of the maximum diameter of defect bubbles at each observation point, and (c) is a statistical chart of the proportion of effective interface bonding area at each observation point. Figure 5 The following are statistical charts showing the initial interface peel strength and failure mode test results of the present invention. Figure (a) is a statistical chart of the average peel force and failure mode of Examples 1-5, and Figure (b) is a statistical chart of the average peel force and failure mode of Comparative Examples 1-5. Figure 6 Figure 1 shows a comparison of the peel strength and retention rate before and after 85 wet heat aging of the present invention. Figure 2(a) is a comparison of the absolute peel strength values of each sample before and after aging, and Figure 3(b) is a comparison of the calculated strength retention rate of each sample. Detailed Implementation
[0030] The technical solutions in the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0031] The main raw materials and reagents used in the following examples and comparative examples have the following sources and specifications. Reagents not specifically mentioned are all commercially available analytical grade or higher grade products.
[0032] Polyester-type thermoplastic polyurethane (TPU): CAS No. 9018-04-6, Shore hardness 85A, melt index 20g / 10min (190℃, 2.16kg), softening point 170℃, industrial grade granules.
[0033] Hydrophobically modified fumed silica: CAS No. 68611-44-9, surface modified with dimethyldichlorosilane, specific surface area BET is 110-150 m² / g. 2 / g, carbon content 0.9~1.2wt%.
[0034] γ-glycidyl etheroxypropyltrimethoxysilane: CAS No. 2530-83-8, purity ≥98%.
[0035] Isophorone diisocyanate dimer resin: CAS No. 53880-05-0, potential NCO content 13.8~14.2%, glass transition temperature Tg 48~52℃, average particle size D90<10μm, internally sealed curing agent without external sealing agent.
[0036] Hydroxyl-terminated hyperbranched polyester: CAS No. 326794-48-3, second-generation hyperbranched polymer, hydroxyl value 490~510mgKOH / g, softening point 85℃, weight-average molecular weight Mw approximately 1750g / mol.
[0037] DBU phenol salt thermosensitive catalyst: a salt complex formed by 1,8-diazabicyclo[5.4.0]undec-7-ene (CAS No. 6674-22-2) and phenol (CAS No. 108-95-2), with a dissociation activation temperature of 100-110℃.
[0038] Butanone (CAS No. 78-93-3) and ethyl acetate (CAS No. 141-78-6) were both of analytical grade.
[0039] Preparation Example 1: This preparation example provides a method for preparing a latently cured mixed micropowder (component D) with a standard stoichiometric ratio, comprising the following steps: (1) Material weighing: Weigh 1000g of isophorone diisocyanate dimer resin (component D1), 375g of hydroxyl-terminated hyperbranched polyester (component D2), and 40g of DBU phenol salt thermosensitive catalyst (component D3); Based on the functional group content of the raw materials, the molar ratio of NCO to OH in the system is about 1:1, and it is in an equivalence equilibrium state.
[0040] (2) Low temperature premixing: The above three solid raw materials are put into a V-type mixer and mixed at 30 rpm for 15 minutes at 25°C to obtain a macroscopically uniform physical mixture.
[0041] (3) Airflow milling: The mixture is fed into a fluidized bed airflow mill for blending and micronization. Cold compressed air treated by a freeze dryer is used as the air source (inlet temperature 5-10℃), the inlet pressure is set to 0.7MPa, the classifier speed is set to 5000rpm, and the outlet temperature is strictly controlled to be below 35℃ to prevent the material from softening and agglomerating due to frictional heat.
[0042] (4) Sieving and collection: The powder is collected by a cyclone separator and passed through a 500-mesh sieve to obtain latent solidified mixed micro powder with a particle size distribution D90 of 8.5 μm, which is then sealed in a moisture-proof container for later use.
[0043] Preparation Example 2: This preparation example provides a method for preparing a latently cured mixed micropowder with a high NCO index (high crosslinking density), comprising the following steps: (1) Material weighing: Weigh 1000g of isophorone diisocyanate dimer resin, 340g of hydroxyl-terminated hyperbranched polyester, and 40g of DBU phenol salt thermosensitive catalyst; at this time, the molar ratio of NCO to OH in the system is about 1.1:1. The slight excess of NCO groups helps to improve the heat resistance of the final cured product and the chemical bonding force to the substrate.
[0044] (2) Low temperature premixing: Put the raw materials into a V-type mixer and mix for 20 minutes at 20°C.
[0045] (3) Airflow pulverization and sieving: The process parameters are the same as in preparation example 1, and a mixed micro powder with a particle size distribution D90 of 8.2 μm is obtained.
[0046] Preparation Example 3: This preparation example provides a method for preparing a highly catalytically active latently solidified mixed micropowder, suitable for low-temperature molds or rapid prototyping processes, including the following steps: (1) Material weighing: Weigh 1000g of isophorone diisocyanate dimer resin, 375g of hydroxyl-terminated hyperbranched polyester, and 60g of DBU phenol salt thermosensitive catalyst; by increasing the catalyst concentration, the activation energy of the ring-opening reaction is reduced, so that it can still be rapidly initiated at a lower temperature.
[0047] (2) Low temperature premixing: Put the raw materials into a V-type mixer and mix for 15 minutes at 20°C.
[0048] (3) Airflow pulverization and sieving: The process parameters are the same as in preparation example 1, and a mixed micro powder with a particle size distribution D90 of 8.8 μm is obtained.
[0049] Preparation Example 4: This preparation example provides a method for preparing a low-thixotropic reactive thixotropic interface anchoring agent (R-TIAA), comprising the following steps: (1) Matrix dissolution: 100g of polyester thermoplastic polyurethane particles were added to a mixed solvent consisting of 200g of butanone and 200g of ethyl acetate and stirred for 3 hours in a constant temperature water bath at 60°C until completely dissolved. Then the mixture was cooled to 25°C.
[0050] (2) Thixotropic construction: 4g of hydrophobic modified fumed silica was added to the solution and dispersed for 20 minutes at a linear velocity of 18m / s using a high shear emulsifier to obtain a translucent base gel with weak thixotropy.
[0051] (3) Loading of active components: Keep the system temperature below 30°C, add 1.5g of γ-glycidyl etheroxypropyltrimethoxysilane and 10g of the latent curing mixed micro powder obtained in Preparation Example 1 to the base adhesive; switch to anchor stirrer and stir and disperse at 80rpm for 30 minutes to make the micro powder uniformly dispersed in the system in a suspended state to avoid high-speed shearing heat generation.
[0052] (4) Degassing: Degas for 10 minutes under a mild vacuum of -0.05MPa to prevent solvent boiling and remove air bubbles entrained during dispersion to obtain a low thixotropic interface anchoring agent.
[0053] Preparation Example 5: This preparation example provides a method for preparing a standard-performance reactive thixotropic interface anchoring agent (R-TIAA) with optimized rheological properties, comprising the following steps: (1) Matrix dissolution: Dissolve 100g of polyester thermoplastic polyurethane particles in 400g of butanone / ethyl acetate (mass ratio 1:1) mixed solvent.
[0054] (2) Thixotropic construction: 6g of hydrophobic modified fumed silica was added and dispersed for 25 minutes at a linear velocity of 20m / s using a high shear disperser to form a gel-like fluid with significant yield stress (does not flow when left to stand).
[0055] (3) Loading of active components: Under the condition of temperature below 35°C, 1.5g of γ-glycidyl etheroxypropyltrimethoxysilane and 14g of the latent curing mixed micro powder obtained in Preparation Example 1 were added and stirred at low speed until uniform.
[0056] (4) Degassing: The material is discharged after degassing using a planetary centrifugal degassing machine. This formula utilizes the synergistic effect of micro powder and gaseous silica to achieve the best balance between positioning ability and bonding strength.
[0057] Preparation Example 6: This preparation example provides a method for preparing a highly thixotropic, enhanced reactive thixotropic interface anchoring agent (R-TIAA), comprising the following steps: (1) Matrix dissolution: Dissolve 100g of polyester thermoplastic polyurethane particles in 420g of butanone / ethyl acetate mixed solvent.
[0058] (2) Thixotropic construction: Add 8g of hydrophobic modified fumed silica and disperse under high shear for 30 minutes to construct a strong physical network.
[0059] (3) Loading of active components: 2.0g of γ-glycidyl ether oxypropyltrimethoxysilane and 18g of the high cross-linking density mixed micro powder obtained in Preparation Example 2 were added at low temperature and dispersed uniformly at low speed.
[0060] (4) Degassing: The process is carried out using a planetary centrifugal degassing machine (due to the high yield stress of the system, centrifugal degassing is required). This formula has a high solid content and rigid filler content, and has extremely high static yield stress, making it suitable for the suspended fixation of large-size FPCs or thick copper FPCs.
[0061] Preparation Example 7: This preparation example provides a method for preparing a fast-curing reactive thixotropic interface anchoring agent (R-TIAA), including the following steps: (1) Matrix dissolution and thixotropic construction: The steps are the same as in Preparation Example 5, and a TPU base adhesive containing 6g of fumed silica is prepared.
[0062] (2) Loading of active components: 1.5g of γ-glycidyl etheroxypropyltrimethoxysilane was added at low temperature (<30℃), and 14g of the highly catalytically active mixed micro powder obtained in Preparation Example 3 was added.
[0063] (3) Degassing: The process is carried out using a planetary centrifugal degassing machine. This formulation has a low reaction initiation temperature and is suitable for sensitive process scenarios with short injection molding holding time (<20s) or low mold temperature (<30℃).
[0064] Example 1: This embodiment provides a standard encapsulation method for embedding FPC into a wearable device mold, using the standard performance reactive thixotropic interface anchoring agent obtained in Preparation Example 5, specifically including the following steps: (1) FPC pretreatment: Select flexible circuit board (FPC) samples, place them in a drying oven and bake them at 120°C for 2 hours to remove the moisture adsorbed on the substrate. After cooling to room temperature, use an atmospheric pressure argon plasma cleaner to treat the surface with a power of 500W and a processing speed of 80mm / s to remove organic contaminants on the surface and activate the polyimide substrate.
[0065] (2) Construction of thixotropic micropiles: Using an automatic dispensing machine, the reactive thixotropic interface anchoring agent (R-TIAA) obtained in Preparation Example 5 was precisely coated onto the edges of the positioning holes and around the main components on the back of the FPC, with the wet film thickness controlled at 40 μm; then the FPC was placed in a tunnel oven and dried at 50°C for 5 minutes, and then heated to 60°C for 5 minutes to ensure solvent evaporation while avoiding premature melting or stickiness of the micropowder. At this point, the coating transformed into a solid pregel layer with a dry feel and high hardness.
[0066] (3) Mold loading: The FPC with the pregel layer is loaded into the cavity of the low-pressure injection mold and the FPC is suspended and fixed by the static friction between the pregel layer and the mold wall; the mold temperature is set to 40℃ and the clamping force is set to 1.5 tons.
[0067] (4) Low-pressure injection molding: Polyester TPU granules are used as the main injection molding material, and the barrel temperature is set to 205℃. The injection molding process is divided into two stages: In the first stage, the melt is injected at a low speed of 8mm / s to 90% of the cavity volume, and the micro-powder phase change endothermic effect of the pregel layer is used to protect the FPC; In the second stage, the holding pressure is switched to 2.5MPa and held for 30 seconds. Under the action of high shear force and melt heat (interface instantaneous temperature of about 120℃) in this stage, the pregel layer undergoes liquefaction and mutual dissolution and triggers the ring-opening crosslinking reaction catalyzed by DBU.
[0068] (5) Post-curing: After cooling for 25 seconds, open the mold and take out the packaged product. Place it in an environment of 25℃ and 50%RH for 24 hours to complete the final chemical cross-linking network construction.
[0069] Example 2: This embodiment provides a sealing method suitable for small and lightweight FPCs, using the low thixotropic interface anchoring agent obtained in Preparation Example 4, and specifically includes the following steps: (1) FPC preprocessing: Same as in Example 1.
[0070] (2) Construction of thixotropic micropiles: The interfacial anchoring agent obtained in Preparation Example 4 was applied to the critical solder joints of the FPC, with a wet film thickness of 30 μm; and dried in a constant temperature oven at 65 °C for 10 minutes. Due to the low filler content of this formulation, the resulting pregel layer has high transparency, which is convenient for visual alignment system identification.
[0071] (3) Mold loading: Place the FPC into the mold and set the mold temperature to 35℃.
[0072] (4) Low-pressure injection molding: The temperature of the main TPU material is 200℃. The injection speed in the first stage is 6mm / s; the holding pressure in the second stage is 2.0MPa, held for 25 seconds. This process utilizes lower viscosity and pressure to achieve non-destructive encapsulation of precision micro-devices.
[0073] (5) Post-curing: Let stand at room temperature for 24 hours.
[0074] Example 3: This embodiment provides a sealing method suitable for large-size or thick copper FPCs, using the high thixotropic, high-filler interface anchoring agent obtained in Preparation Example 6, and specifically includes the following steps: (1) FPC preprocessing: Same as in Example 1.
[0075] (2) Construction of thixotropic micropiles: The interfacial anchoring agent obtained in Preparation Example 6 was applied to the periphery and warp-prone areas of a large-size FPC, with a wet film thickness of 50 μm; segmented drying: 60℃ / 5min + 70℃ / 5min. The resulting pregel layer has high hardness and extremely strong erosion resistance.
[0076] (3) Mold loading: The mold temperature is set to 45℃. After the FPC is put into the mold, the heavy FPC is firmly clamped in the mold cavity using high-modulus pregel micropiles.
[0077] (4) Low-pressure injection molding: The temperature of the main TPU material is 210℃. The injection speed in the first stage is 10mm / s; the holding pressure in the second stage is 3.0MPa, held for 35 seconds. The high shear force ensures the full flow and interface fusion of the high-fill coating.
[0078] (5) Post-curing: Let stand at room temperature for 24 hours.
[0079] Example 4: This embodiment provides a sealing method suitable for low-temperature mold processes. To prevent product shrinkage and deformation, a lower mold temperature is used. The method specifically includes the following steps: (1) FPC preprocessing: Same as in Example 1.
[0080] (2) Thixotropic micropiles were constructed by coating with the fast-curing interface anchoring agent (high catalytic activity) obtained in Preparation Example 7; the drying process was to dry at 60°C for 15 minutes.
[0081] (3) Mold loading: The mold temperature is set to 25℃ (cold mold process).
[0082] (4) Low-pressure injection molding: The temperature of the main TPU material is 200℃. The injection speed in the first stage is 10mm / s; the holding pressure in the second stage is 2.5MPa, held for 20 seconds. Due to the high concentration of catalyst in the formula, even under the environment of rapid decay of interface temperature caused by cold mold, it can still quickly initiate ring-opening crosslinking and establish initial strength within the holding pressure window period.
[0083] (5) Post-curing: Let stand at room temperature for 24 hours.
[0084] Example 5: This embodiment provides a sealing method for applications requiring higher resistance to high-temperature aging. It utilizes the anchoring agent containing high-crosslinking density micropowder as described in Example 6, and specifically includes the following steps: (1) FPC preprocessing: Same as in Example 1.
[0085] (2) Thixotropic micropiles were constructed: the interface anchoring agent (excess NCO formulation) obtained in Preparation Example 6 was used to coat the FPC; the drying process was to dry at 70°C for 15 minutes.
[0086] (3) Mold loading: Mold temperature 40℃.
[0087] (4) Low-pressure injection molding: The temperature of the main material TPU is 210℃, the holding pressure is 2.8MPa, and the holding time is extended to 40 seconds to ensure the full reaction of the high-density cross-linked network.
[0088] (5) Post-curing: Let stand at room temperature for 24 hours. The product obtained in this example is expected to have better resistance to peel strength under humid heat aging.
[0089] Comparative Example 1: Compared with Example 1, the difference is that the "thixotropic micropile construction" step is omitted, that is, the FPC is not coated, and after plasma cleaning, it is directly put into the mold for low-pressure injection molding and encapsulation. All other aspects are the same.
[0090] Comparative Example 2: Compared with Example 1, the difference is that hydrophobically modified fumed silica (component B) was not added in the preparation process of the interface anchoring agent, while the other raw materials and process steps are the same.
[0091] Comparative Example 3: Compared with Example 1, the difference is that no latent curing mixed micro powder (component D) was added during the preparation of the interface anchoring agent. Physical bonding was achieved solely through the TPU matrix and silane coupling agent. All other aspects remained the same.
[0092] Comparative Example 4: Compared with Example 1, the difference is that in the preparation of the interface anchoring agent, the latent curing mixed micro powder (component D) is not used, but an equivalent amount of methyl ethyl ketone oxime (MEKO) blocked isophorone diisocyanate curing agent is added (directly added to the base adhesive for dispersion), and the rest are the same.
[0093] Comparative Example 5: Compared with Example 1, the difference is that no DBU phenol salt thermosensitive catalyst (component D3) was added during the preparation of the latent solidification mixed micro powder (component D), while all other aspects are the same.
[0094] Test Example 1: Rheological Properties and Thixotropic Behavior Test Experimental Description: The experiment was conducted using an AntonPaar MCR 302 rotational rheometer equipped with a Peltier temperature control system. The test fixture was a CP25-2 cone-plate system with a diameter of 25 mm and a cone angle of 2°. The truncation was set to 0.105 mm. The ambient temperature was controlled at 25 ± 0.1℃.
[0095] The specific experimental steps are as follows: The sample to be tested was placed in a constant temperature environment of 25℃ for equilibration for 2 hours. Approximately 0.2 mL of sample was placed in the center of the rheometer measuring plate, the upper cone plate was lowered to the measuring position, and the excess adhesive at the edge was scraped off. The sample was allowed to stand for 300 seconds to allow for microstructure reconstruction.
[0096] Yield stress scanning was performed using the controlled shear stress (CSS) mode. The shear stress loading ranged from 0.1 Pa to 1000 Pa (logarithmic growth). The shear stress value at which the storage modulus (G') equaled the loss modulus (G") was recorded as the static yield stress.
[0097] After resampling and allowing it to stand, a steady-state flow curve scan was performed. The shear rate range was set to 0.1 s⁻¹. -1 up to 100s -1 The apparent viscosity at different shear rates was recorded.
[0098] The thixotropic index (TI) is calculated using the following formula: at low shear rates (0.1 s⁻¹), the thixotropic index is... -1 The viscosity value at the high shear rate (100 s) divided by the viscosity value at the high shear rate (100 s) -1 The viscosity value at ( ).
[0099] Experimental data: Table 1: Rheological parameter test results of each embodiment and comparative sample Sample number Static yield stress (Pa) <![CDATA[Low shear viscosity (η 0.1 , Pa·s)]]> <![CDATA[High shear viscosity (η 100 , Pa·s)]]> Thixotropic index (TI) Example 1 342.6 4285.0 4.81 890.8 Example 2 115.3 1450.5 3.92 370.0 Example 3 587.9 7350.2 5.64 1303.2 Comparative Example 2 3.80 5.45 4.31 1.26 Results Analysis and Conclusions: according to Figure 1 According to the data in Table 1, the thixotropic indices of samples 1, 2, and 3 are all much greater than 1, exhibiting characteristics of a strongly pseudoplastic fluid. The static yield stress of Example 1 is 342.6 Pa, and the thixotropic index is 890.8. Under static or low shear field conditions (corresponding to 0.1 s⁻¹), -1 The ultra-high viscosity hydrophobic fumed silica and micro-powder filler formed a physical network structure in the TPU matrix that could resist gravity and injection molding impact; under a high shear field (corresponding to 100s), -1 When the apparent viscosity drops to 4.81 Pa·s, the physical network disintegrates, and the material transforms into a free-flowing liquid.
[0100] In Example 3, the increased content of hydrophobic fumed silica and solid filler increased the static yield stress to 587.9 Pa and the thixotropic index to 1303.2, indicating the formation of a higher density physical cross-linked network within the system, corresponding to higher static structural strength. Example 2 reduced the amount of thixotropic agent, decreasing the static yield stress to 115.3 Pa and lowering the low-shear viscosity, while still maintaining shear-thinning characteristics.
[0101] Comparative Example 2, without the addition of hydrophobically modified fumed silica, exhibited extremely low static yield stress (3.80 Pa), a thixotropic index of 1.26, and minimal difference between low and high shear viscosities. These data indicate that Comparative Example 2 closely resembles a Newtonian fluid and lacks an internal skeletal structure capable of resisting external stress. Without external force, this material cannot maintain a fixed shape, confirming the necessity of hydrophobically modified fumed silica for constructing statically positioned micropiles.
[0102] Test Example 2: Thermal Latency and Curing Kinetics Test Experimental description: The experiment used a Mettler Toledo DSC 3+ differential scanning calorimeter equipped with an automated sample introduction system. The experimental atmosphere was set to high-purity nitrogen (N2), and the gas flow rate was controlled at 50 mL / min.
[0103] The specific experimental steps are as follows: Preparation of test dry films: The liquid samples from Examples 1, 4, and Comparative Example 5 were coated onto the surface of polytetrafluoroethylene (PTFE) release films. They were placed in a forced-air drying oven and subjected to the drying process corresponding to each example (e.g., 60℃ / 5min + 80℃ / 3min). After the solvent had completely evaporated, the films were cooled to room temperature and peeled off to obtain uncured pre-gelled dry film samples.
[0104] Weighing and Packaging: Take the dried film sample, cut it into small pieces, and accurately weigh 5.0 mg to 8.0 mg into a 40 μL standard aluminum crucible. Cover the crucible and seal it using a tablet press. Use an empty aluminum crucible of the same specifications as a reference.
[0105] Dynamic scanning: The temperature scanning program is started under nitrogen protection. The starting temperature is set to 25℃, the ending temperature is set to 200℃, and the heating rate is set to 10K / min. The instrument automatically records the heat flow curve of the sample as a function of temperature.
[0106] Data analysis: The heat flux curve was integrated using STARE software. The physical melting peak temperature of the endothermic peak was determined. ) and enthalpy of fusion ( ); The reaction initiation temperature for determining the exothermic peak ( ), peak reaction temperature ( ) and the exothermic enthalpy of the reaction ( ).
[0107] Experimental data: Table 2: Kinetic parameters of thermorheological phase transition and solidification of each component system Sample number Physical melting peak temperature (°C) enthalpy of melting (J / g) Curing reaction start temperature (°C) peak temperature of curing reaction (°C) Example 1 78.4 12.6 108.2 127.5 Example 4 76.9 11.9 94.7 112.3 Comparative Example 5 79.1 13.2 Not detected (<180℃) - Results Analysis and Conclusions: according to Figure 2 According to the data in Table 2, physical melting endothermic peaks were detected in Examples 1 and 4 in the range of 76°C to 80°C, with Tm values of 78.4°C and 76.9°C, respectively, corresponding to melting endothermic enthalpies. The values are 12.6 J / g and 11.9 J / g, respectively. This endothermic signal corresponds to the solid-liquid phase transition process of component D (micronized urea diketone resin and hyperbranched polyester). At the instant the injection melt contacts the coating, this physical phase transition process absorbs heat, which aligns with the design expectation of reducing FPC thermal shock using phase transition enthalpy.
[0108] Regarding chemical reaction kinetics, the curing reaction initiation temperature in Example 1... The temperature reached 108.2℃, higher than the highest drying temperature (80℃) during the FPC pretreatment stage. This data indicates that the formulation was chemically inert during the solvent evaporation stage, without early pre-curing, ensuring the film quality and subsequent wetting ability of the coating. Its peak reaction temperature... The temperature is 127.5℃, which matches the temperature range (120~130℃) of the melt transfer to the interface in the low-pressure injection molding process, thus promoting the construction of the cross-linked network during the holding pressure stage.
[0109] Example 4 increased the concentration of DBU phenolic salt catalyst, which It dropped to 94.7℃. The temperature was shifted to 112.3℃. The kinetic characteristics indicate that the reaction barrier of this formulation is lowered, making it suitable for low-temperature molding processes or packaging of heat-sensitive devices, and enabling the locking of the semi-interpenetrating network (Semi-IPN) under lower heat input.
[0110] Comparative Example 5 only observed a physical melting peak within the scanning range, and no effective exothermic reaction peak (<180℃) was detected. This result confirms that in the absence of a temperature-sensitive catalyst, the ring-opening activation energy of the isocyanate dimer is too high, making it impossible to initiate an addition reaction within the temperature and time window provided by the injection molding process. This, in turn, verifies the necessity of a catalytic ring-opening mechanism for achieving in-situ curing.
[0111] Test Example 3: FPC Packaging Positioning Accuracy Test (Anti-dumping Capability) Experimental Description: The experiment used a high-precision 2D image measuring instrument (model: VMM-3020D), with an optical magnification set to 0.7X~4.5X and a measurement accuracy of ≤(3+L / 200)μm. The test samples were the finished products of Examples 1-5 and Comparative Examples 1-3 after low-pressure injection molding. Twenty samples were randomly selected from each group for statistical analysis.
[0112] The specific experimental steps are as follows: The packaged FPC sample is placed on the glass stage of the image measuring instrument. The intensity of the backlight and the ring light is adjusted so that the internal circuit features of the FPC are still clearly visible after passing through the semi-transparent encapsulation layer.
[0113] Establish a measurement coordinate system. Select the feature hole left by the mold positioning post or the reference edge of the product appearance as the reference origin (Datum) to correct the workpiece placement angle deviation.
[0114] Automatically capture the geometric center coordinates of the critical pads (Pads) on the FPC. Record the measured values of this center point relative to the standard coordinates of the CAD design in the X and Y axes.
[0115] Calculate the offset vector distance, which is the straight-line distance between the measured coordinates and the theoretical coordinates. Take the maximum offset value among the 20 samples in each group as the final evaluation index for that group to assess the positioning limit under the worst working conditions.
[0116] Experimental data: Table 3: Statistics of FPC position offset after encapsulation of each component system Sample number Sample size (n) Maximum X-axis offset (mm) Maximum Y-axis offset (mm) Maximum offset of composite vector (mm) Judgment result Example 1 20 0.054 0.048 0.072 qualified Example 2 20 0.089 0.092 0.128 qualified Example 3 20 0.032 0.021 0.038 Excellent Example 4 20 0.061 0.055 0.082 qualified Example 5 20 0.058 0.063 0.086 qualified Comparative Example 1 20 1.425 2.110 2.546 Serious failure Comparative Example 2 20 0.892 1.104 1.419 Failure Comparative Example 3 20 0.415 0.388 0.568 Excessive deviation Results Analysis and Conclusions: according to Figure 3 According to the data in Table 3, the maximum overall vector offset for Examples 1 to 5 is less than 0.13 mm, which meets the dimensional tolerance requirement of ±0.15 mm for precision electronic packaging. Specifically, the maximum overall vector offset for Example 3 is 0.038 mm. This result is related to the high content of hydrophobic fumed silica and micronized filler in its formulation. The high filler content system constructs an interface layer with a yield stress of 587.9 Pa. This interface layer forms a physical confinement structure in the early stages of injection molding, resisting the shear stress generated on the FPC by the melt flow front.
[0117] The maximum offset of Comparative Example 1 (blank control) was 2.546 mm. This data indicates that without interface anchoring treatment, the FPC lacks fixed constraints within the mold cavity and undergoes displacement under fluid pressure.
[0118] Comparative Example 2 (without hydrophobic fumed silica) showed a shift of 1.419 mm. This result indicates that the viscosity of the thermoplastic polyurethane matrix alone cannot balance the impact of the injection molding fluid. Due to the lack of a physical thixotropic framework constructed from hydrophobic fumed silica, the coating did not exhibit high yield stress characteristics and experienced rheological yielding in the early stages of injection molding, leading to positioning failure.
[0119] The offset of Comparative Example 3 (without micronized filler) was 0.568 mm. Although this system retained hydrophobic fumed silica, it lacked the particle reinforcement effect provided by component D (micronized urea diketone resin and hyperbranched polyester). The absence of solid filler led to a decrease in the dry film modulus and interfacial static friction coefficient of the coating, resulting in creep displacement during the holding pressure stage. This result verifies the synergistic effect of particle reinforcement and thixotropic framework in the static rheological positioning mechanism.
[0120] Test Example 4: Assessment of Macroscopic Defects and Bubble Rate at the Interface Experimental Description: The experiment was conducted using a Keyence VHX-7000 series ultra-depth-of-field 3D microscope.
[0121] The specific experimental steps are as follows: Sampling and mounting: The interface bonding area after encapsulation of Example 1 and Comparative Example 4 was cut out respectively, and the sample size was controlled to be 10mm×10mm. The sample was vertically fixed in the mold using cold mounting resin (epoxy resin to curing agent mass ratio 3:1), and vacuum degassing was performed in a vacuum drying oven, followed by room temperature curing for 24 hours.
[0122] Grinding and polishing: Using an automatic metallographic grinding machine, wet grinding was performed sequentially using 320-grit, 800-grit, 1200-grit, and 2000-grit silicon carbide sandpaper to remove the cutting stress layer. Subsequently, polishing was performed using 1μm and 0.05μm alumina polishing slurries until the cross-section was mirror-finished and free of visible scratches.
[0123] Microscopic observation: The polished sample was placed on the microscope stage, and images of the interface between the FPC and the injection molding material were captured using coaxial incident light illumination mode at 200x and 500x magnification.
[0124] Data statistics: Using image analysis software, a standard grid of 1mm × 1mm was superimposed within the field of view. The number of bubbles or cavities with a diameter greater than 5μm within the grid area was counted, and the bubble density (number of bubbles / mm²) was calculated. 2 Simultaneously, using the grayscale threshold segmentation method, the percentage of pixels in the fully wetted area of the adhesive at the interface is calculated to obtain the effective interface bonding area percentage.
[0125] Experimental data: Table 4: Statistical Data on Interface Bubble Density and Bonding Area Sample number Observation area points <![CDATA[Bubble / pinhole density (pieces / mm 2 )]]> Maximum bubble diameter (μm) Effective interface integration area percentage (%) Example 1 Point 1 (Center) 0 - 99.92 Point 2 (edge) 0 - 99.85 Point 3 (R-angle) 0.2 8.4 99.51 Comparative Example 4 Point 1 (Center) 18.6 125.3 68.45 Point 2 (edge) 14.2 89.6 74.22 Point 3 (R-angle) 22.1 148.7 62.18 Results Analysis and Conclusions: according to Figure 4 According to the data in Table 4, in Example 1, the bubble density at different observation points was close to 0, and the average effective interface bonding area ratio remained above 99.7%. Occasional micro-voids (point 3, 0.2 / mm) were observed. 2 The gas generation is attributed to physical gas entrapment during the injection molding process rather than chemical gas generation. This result indicates that, based on the ring-opening addition reaction mechanism of micronized urea diketone resin (component D1), only the opening of the four-membered ring and the addition of hydroxyl groups occur during the high-temperature curing process. No small molecule byproducts are generated throughout the entire chemical process, thus ensuring the compactness and continuity of the interface.
[0126] The bubble density of Comparative Example 4 ranged from 14.2 to 22.1 bubbles / mm².2 The data shows that the maximum bubble diameter reached 148.7 μm, and the effective interfacial bonding area decreased to a minimum of 62.18%. This data confirms that when using methyl ethyl ketone oxime (MEKO) blocked isocyanate curing agent, a deblocking reaction occurs within the injection molding temperature range of 110℃ to 130℃, releasing gaseous methyl ethyl ketone oxime molecules. Since the injection melt is already in the holding pressure and cooling stage at this time, the viscosity increases rapidly, and the released gas cannot escape the system, accumulating at the interface to form high-pressure gas pockets, leading to localized separation of the adhesive layer from the FPC substrate.
[0127] The comparative results show that using the ring-opening addition mechanism of urea diketone to replace the traditional sealing agent desealing mechanism eliminates the interface defects caused by chemical foaming and ensures the integrity of the encapsulation structure.
[0128] Test Example 5: Initial Interface Peel Strength Test Experimental Description: The experiment was conducted using a universal testing machine (model: Instron5966) equipped with a 500N load cell. The test environment was controlled at a temperature of 23±2℃ and a relative humidity of 50±5%.
[0129] The specific experimental steps are as follows: Preparation of peel test specimens: The packaged products of Examples 1-5 and Comparative Examples 1-5 were cut into standard strips 10 mm wide and 100 mm long. For samples with a relatively hard injection molding layer, the flexible FPC substrate end was used as the peel end, and the injection molding layer was fixed to the rigid base; for double flexible structures, both ends were directly clamped.
[0130] Parameter setting and clamping: Clamp the free end of the sample in the upper and lower clamps of the testing machine, and adjust the clamp spacing to keep the peel angle at 90 degrees (a special 90-degree peel slide is required). Set the tensile rate to 50 mm / min.
[0131] Data Acquisition: Start the stretching program and record the load-displacement curve. Discard the unstable data in the first 5mm and last 5mm, and calculate the arithmetic mean of the load data in the middle stable section (at least 20mm of stroke).
[0132] Failure Mode Observation: After the test, the fracture state of the peel surface is observed with the naked eye and a 10x magnifying glass to determine the failure mode. If the fracture occurs inside the adhesive layer or the injection molding material itself, it is determined to be cohesive failure (CF); if the fracture occurs at the interface between the adhesive layer and the FPC, it is determined to be interfacial failure (AF); if the FPC cover film is torn, it is determined to be substrate failure (SF).
[0133] Experimental data: Table 5: Test results of initial interfacial peel strength and failure mode of each component system Sample number Average peel force (N / cm) Minimum value (N / cm) Maximum value (N / cm) Destruction Mode Example 1 18.42 17.1 19.5 100% cohesion breaking (CF) Example 2 16.85 15.9 17.6 90% cohesion failure / 10% interface failure Example 3 19.14 18.2 20.3 100% cohesion breaking (CF) Example 4 18.91 17.5 20.1 100% cohesion breaking (CF) Example 5 21.03 19.8 22.4 Substrate damage (SF, FPC cover film tearing) Comparative Example 1 2.15 1.8 2.5 100% Interface Destruction (AF) Comparative Example 2 13.47 8.2 15.1 Hybrid damage (AF / CF) Comparative Example 3 7.62 6.9 8.4 100% Interface Destruction (AF) Comparative Example 4 5.33 4.1 6.2 Interface damage (breakage at the bubble) Comparative Example 5 8.11 7.5 8.8 100% Interface Destruction (AF) Results Analysis and Conclusions: according to Figure 5 According to the data in Table 5, the average peel strength of Examples 1 to 5 ranged from 16.85 N / cm to 21.03 N / cm, mainly exhibiting cohesive failure or substrate failure. This indicates that the interfacial bonding force exceeded the strength of the adhesive layer or the FPC substrate. Specifically, Example 1 achieved a strength of 18.42 N / cm, confirming that under the catalysis of DBU phenolate, the micronized urea diketone resin underwent ring-opening at the high temperature of injection molding. The resulting active isocyanate groups reacted with the active hydrogen on the TPU matrix and FPC surface, forming a high-crosslink density urea formate bond, constructing a stable semi-interpenetrating network (Semi-IPN). Example 5, due to its high-crosslinking formulation, achieved a strength of 21.03 N / cm, resulting in the FPC cover film tearing first during the peel process.
[0134] Comparative Example 1 (blank control) showed a peel force of only 2.15 N / cm, and it was a complete interface failure, indicating that there are only weak intermolecular forces between the untreated FPC polyimide surface and the injection-molded TPU, which cannot meet the encapsulation requirements.
[0135] Comparative Example 3 (without micronized urea diketone component) had a peel strength of 7.62 N / cm, which was determined to be interfacial failure. This data reflects that the bonding strength relying solely on the physical melt bond of the TPU prepolymer (mainly hydrogen bonding) is significantly lower than the chemical bonding strength in the examples.
[0136] The peel strength of Comparative Example 5 (without catalyst) was 8.11 N / cm, which was close to that of Comparative Example 3. Combined with the DSC data of Test Example 2, it can be seen that in the absence of a temperature-sensitive catalyst, the urea diketone ring did not undergo a ring-opening reaction and failed to form a chemical cross-linked network. The system degenerated into ordinary physical adhesion, further verifying the decisive role of "in-situ catalytic ring-opening" in constructing chemical anchoring.
[0137] Comparative Example 4 (MEKO closed type) has a strength of only 5.33 N / cm, which is lower than that of Comparative Examples 3 and 5. This is because the densely distributed bubble defects at the interface (refer to the results of Test Example 4) reduce the effective bonding area and become stress concentration points, causing the interface to fail prematurely under lower loads.
[0138] Test Example 6: Reliability Test for Damp Heat Aging Experimental Description: The experiment used a programmable constant temperature and humidity test chamber (model: Espec PL-3J) for accelerated aging treatment, and combined it with a universal testing machine for mechanical characterization.
[0139] The specific experimental steps are as follows: The packaged products of Examples 1, 5, 3, and 5 were selected as test samples, and 10 standard samples were prepared for each group. The average initial peel strength of each group of samples before aging was recorded (see data from Test Example 5).
[0140] The samples were suspended vertically on the sample rack inside the test chamber, ensuring that the samples did not touch each other and that airflow was unobstructed. The test chamber temperature was set to 85℃ and the relative humidity to 85%RH. Timing began after the temperature and humidity inside the chamber reached the set values, and the aging time was 168 hours.
[0141] After aging, the sample was removed and placed in a standard laboratory environment (23℃, 50%RH) for 24 hours to eliminate the instantaneous effect of damp heat on the material modulus and allow the moisture content to reach equilibrium.
[0142] Perform a 90-degree T-shaped peel strength test according to the method described in Test Example 5. Record the average peel force after aging and calculate the strength retention rate according to the formula: Strength retention rate = (peel strength after aging / initial peel strength) × 100%.
[0143] Experimental data: Table 6: Comparison of Peel Strength and Retention Rate Before and After Double 85 Wet Heat Aging Sample number Initial peel strength (N / cm) Peel strength after aging (N / cm) Strength retention rate (%) Post-aging damage modes Example 1 18.42 16.24 88.16% Cohesion failure (CF) Example 5 21.03 20.15 95.81% Substrate failure (SF) Comparative Example 3 7.62 1.48 19.42% Interface Destruction (AF) Comparative Example 5 8.11 2.85 35.14% Interface Destruction (AF) Results Analysis and Conclusions: according to Figure 6 Table 6 shows that after undergoing harsh humid heat aging (85℃ / 85%RH / 168h), Examples 1 and 5 maintained strengths of 88.16% and 95.81%, respectively. The residual strength of Example 1 was 16.24 N / cm, significantly higher than the initial strength of the comparative example. Example 5 exhibited the best weather resistance, but substrate failure still occurred after aging. These results indicate that the allophanate chemical bonds generated by ring-opening of micronized urea diketone resin induced by a temperature-sensitive catalyst possess excellent hydrolytic stability. This chemical bonding and the semi-interpenetrating network (Semi-IPN) structure tightly lock the interface, making it difficult for moisture to penetrate to the bonding sites, thus maintaining the integrity of the connection under high temperature and high humidity conditions.
[0144] Comparative Example 3 (without chemical crosslinking) showed a strength retention rate of only 19.42%, with the peel strength plummeting from 7.62 N / cm to 1.48 N / cm, and the failure mode being complete interfacial separation. This confirms that physical adhesion mainly relies on van der Waals forces and hydrogen bonding. Under the double 85 environment, water molecules readily penetrate the interface and compete with the polymer chains for hydrogen bonds, leading to desorption from physical adsorption sites, i.e., a typical "water displacement" effect, resulting in almost complete loss of interfacial adhesion.
[0145] Comparative Example 5 (without catalyst) retained 35.14% of its strength, but the strength decreased to 2.85 N / cm after aging. Although the residual strength was slightly higher than that of Comparative Example 3 (presumably because unreacted filler particles increased the impermeability pathway of the adhesive layer itself), it still showed a significant overall decline. This data further corroborates the conclusion of Test Example 5: in the absence of a catalyst, the diurene ring failed to open and form chemical bonds during injection molding. The system is essentially still a physical bond and cannot resist the erosion of a humid and hot environment.
[0146] In summary, chemical bonding (example) and physical bonding (comparative example) differ fundamentally in terms of environmental reliability. The reactive micronized powder system of this invention can transform short-term physical positioning into long-term chemical anchoring, solving the problem of insufficient reliability of traditional physical bonding under harsh conditions.
[0147] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A sealing method for embedding FPC into a wearable device mold, characterized in that, Includes the following steps: S1. FPC Pretreatment: Cleaning and activation treatment of the surface of the flexible circuit board (FPC); S2. Construction of thixotropic micropiles: A reactive thixotropic interface anchoring agent is coated at a predetermined position on the FPC. After drying to remove the solvent, a solid pregel layer with thixotropic properties is formed. S3. Mold loading: The FPC with the pregel layer is loaded into the injection mold cavity, and the FPC is suspended and fixed by the friction between the pregel layer and the mold wall. S4. Low-pressure injection molding encapsulation: Thermoplastic polyurethane melt is injected into the mold cavity. During the pressure holding stage, the heat of the melt is used to initiate a phase change, mutual solubility and cross-linking reaction in the pregel layer to complete the encapsulation. The reactive thixotropic interface anchoring agent is made from the following raw materials in parts by weight: 100 parts of polyester thermoplastic polyurethane, 400-420 parts of mixed solvent, 4-8 parts of hydrophobic modified fumed silica, 1.5-2.0 parts of silane coupling agent, and 10-18 parts of latent curing mixed micro powder. The latent curing mixed micro powder contains isophorone diisocyanate dimer resin and a temperature-sensitive catalyst. In step S4, the latent curing mixed micro powder undergoes a ring-opening reaction of the diurene ring under the activation of the injection molding melt temperature, forming chemical bonds with the thermoplastic polyurethane melt and the FPC surface.
2. The sealing method for embedding FPC into a wearable device mold according to claim 1, characterized in that, The latent solidification mixed micro powder is made from the following components in parts by weight: 100 parts of isophorone diisocyanate dimer resin; 34–37.5 parts of hydroxyl-terminated hyperbranched polyester; 4-6 parts of DBU phenol salt thermosensitive catalyst.
3. The sealing method for embedding FPC into a wearable device mold according to claim 1, characterized in that, The method for preparing the latent solidified mixed micro powder includes: The isophorone diisocyanate dimer resin, hydroxyl-terminated hyperbranched polyester and temperature-sensitive catalyst are premixed at 20-25°C, and then airflow pulverization is performed using cold compressed air with an inlet temperature of 5-10°C as the air source. The outlet temperature is controlled to be below 35°C, and the powder with a particle size distribution D90 of 8.2-8.8 μm is obtained by sieving.
4. The sealing method for embedding FPC into a wearable device mold according to claim 1, characterized in that, In step S2, the preparation method of the reactive thixotropic interface anchoring agent is as follows: A thixotropic adhesive was constructed by dissolving polyester-type thermoplastic polyurethane in a mixed solvent, adding hydrophobically modified fumed silica, and dispersing it under high shear at a linear velocity of 18–20 m / s. Subsequently, at a temperature below 35°C, the silane coupling agent and the latently cured mixed micro powder were added, dispersed uniformly at a low speed, and degassed.
5. The sealing method for embedding FPC into a wearable device mold according to claim 1, characterized in that, The mixed solvent is a mixture of butanone and ethyl acetate; the silane coupling agent is γ-glycidyl etheroxypropyltrimethoxysilane.
6. The sealing method for embedding FPC into a wearable device mold according to claim 1, characterized in that, In step S1, FPC preprocessing includes: The FPC was baked and dried at 120°C, and after cooling, it was surface activated using an atmospheric pressure argon plasma cleaner with a processing power of 500W.
7. The sealing method for embedding FPC into a wearable device mold according to claim 1, characterized in that, In step S2, the drying process adopts one of the following methods: Method 1: Dry at a constant temperature of 50-70℃ for 10-15 minutes; Method 2: First dry at 50-60℃ for 5-15 minutes, then dry at 60-70℃ for 5-15 minutes.
8. The sealing method for embedding FPC into a wearable device mold according to claim 1, characterized in that, In step S4, the low-pressure injection molding encapsulation process employs a two-stage procedure: First stage: Fill 90% of the cavity volume with an injection speed of 6-10 mm / s; Second stage: Maintain a holding pressure of 2.0–3.0 MPa for 20–40 seconds; The barrel temperature of the thermoplastic polyurethane melt is 200–210°C, and the mold temperature is 25–45°C.
9. The sealing method for embedding FPC into a wearable device mold according to claim 1, characterized in that, The ring-opening reaction is: Under the action of a temperature-sensitive catalyst, the four-membered ring structure of the isophorone diisocyanate dimer in the latent solidified mixed micro powder opens at an instantaneous interfacial temperature of 110–130°C to generate isocyanate groups, which then react with the active hydrogen on the thermoplastic polyurethane melt and the FPC surface to form urea carbamate bonds, thus forming a semi-interpenetrating network structure.
10. The sealing method for embedding FPC into a wearable device mold according to claim 1, characterized in that, The method further includes an S5 post-curing step: After injection molding, the packaged product is placed in an environment of 20-25℃ and 50%RH relative humidity and left to stand for 24 hours.
Citation Information
Patent Citations
High and low temperature impact resistant functional polyurethane coating material and preparation process thereof
CN121160208A
Composite polyurethane anti-erosion protective adhesive tape and preparation method thereof
CN121450248A